Negociando la inclusión al mercado de consumo: los programas de transferencias condicionadas de dinero y el orden familiar = Negotiating inclusion into the consumption market: conditional cash transfer programs and family order - Wilkis, Ariel; Hornes, Martin (Civitas - Revista de Ciências Sociais)
This paper explores two processes that agendas of economic sociology research normally addresse separately: the processes of financialization of consumption and monetization of social policies in the popular sectors. Through ethnographic work carried out in the Buenos Aires metropolitan area, we suggest looking into the new monetary infrastructure of the popular world where different monetary segments converge and (finance and social policy) and show the new economic reality of the popular sectors